The Determination of Antioxidant Activity of Senna Alexandrina Leaves and Phoenix Dactylifera Fruits for Food Preservation - Muhamad Mahir, Muhammad Nourhakeem; Mohamed Rehan, 'Aisyah; Mohd Fauzi, Noor Akhmazillah (Progress in Engineering Application and Technology, 2023)
A sustainable approach in food preservation is by using natural resources, contributing to the overall sustainability of food supply chain. Synthetic preservatives such as nitrates, sorbate, and phenolic antioxidants can cause harmful effects to consumers such as allergy reaction. Preserving food using natural products containing antioxidant or antimicrobial properties can be an alternative to other preservation methods i.e., thermal, or chemical methods. These methods can increase food shelf life from spoilage microorganism that alter the food texture, edibility, and nutritional values (antimicrobial) and delaying or preventing rancidity of food due to oxidation (antioxidant). Senna alexandrina, an ornamental shrub that grows natively in Egypt and commonly used as an herbal tea, and Phoenix dactylifera commonly known as date palms are being the focus of this study, aimed to determine its’ antioxidant activity for food preservation application. The highest antioxidant activity for TPC is observed in S. alexandrina leaves extract dissolved in methanol for each concentration tested. This study showed that methanol is the most effective solvent for phenolic extraction. Accordingly, the highest antioxidant activity in DPPH scavenging assay is observed from 1 mL S. alexandrina leaves extract with methanol solvent (65.59 %). Meanwhile, the highest antioxidant activity for P. dactylifera fruit extract is observed from 5 mL extract in ethanol solvent (83.53 %). The presence of antioxidant compound was determined by the presence of peaks of hydroxyl (-OH) group using infrared FTIR spectroscopy. In addition, observation of both S. alexandrina and P. dactylifera extracts’ application on homemade bread showed promising results, with less mould growth compared to homemade bread without any additive, as well as in comparison to homemade bread with BHA added. Further studies on these findings will be beneficial to explore the potential of these natural food preservatives.